Methods for determining iodine in urine - Larisa V. Nikankina; Zamira T. Zuraeva; Ekaterina A. Troshina (ZAO "Consilium Medicum", 2023)
Iodine deficiency remains a serious threat to public health worldwide, especially in children and pregnant women. Despite the apparent ease of iodine deficiency elimination with the help of a simple and highly effective strategy of compulsory salt iodization, the problem of iodine deficiency and iodine deficiency disorders remains urgent for public health in the Russian Federation. The most effective and informative way to study iodine status at population level is determination of iodine concentration in urine in epidemiological studies. This article presents a review of urinary iodine determination methods, as well as methodological recommendations for iodine determination, developed and adopted in National Medical Research Center for Endocrinology.